A mononuclear five-coordinate Co(ii) single molecule magnet with a spin crossover between the S = 1/2 and 3/2 states. Issue 46 (12th November 2018) - Chen, Lei; Song, Jingbo; Zhao, Wen; Yi, Gangji; Zhou, Zhikuan; Yuan, Aihua; Song, You; Wang, Zhenxing; Ouyang, Zhong-Wen
Abstract : A mononuclear cobalt(ii ) complex with square pyramidal geometry displays a spin transition with a small hysteresis loop and slow magnetic relaxation. Abstract : Although a great number of single-ion magnets (SIMs) and spin-crossover (SCO) compounds have been discovered, multifunctional materials with the combination of SCO and SIM properties are extremely scarce. Here magnetic studies have been carried out for a mononuclear, five-coordinate cobalt(ii ) complex [Co(3, 4-lut)4 Br]Br (1 ) with square pyramidal geometry. Direct-current magnetic measurement confirms the spin transition between the S = 1/2 and 3/2 states in the range of 150–290 K with a small hysteresis loop. Frequency- and temperature-dependent alternating-current magnetic susceptibility reveals slow magnetization relaxation under an applied dc field of 3000 Oe. The work here presents the first instance of the five-coordinate mononuclear cobalt(ii )-based SIM exhibiting the thermally induced complete SCO.